Development of Leishmania (Mundinia) in guinea pigs ... : تطور الليشمانيا (موندينيا) في خنازير غينيا ... - Tomáš Bečvář; Padet Siriyasatien; Paul A. Bates; Petr Volf; Jovana Sádlová (OpenAlex, 2020)
Leishmaniasis is a human and animal disease caused by parasites of the genus Leishmania, which is now divided into four subgenera, Leishmania, Viannia, Sauroleishmania and Mundinia. Subgenus Mundinia, established in 2016, is geographically widely dispersed, its distribution covers all continents, except Antarctica. It consists of 5 species; L. enriettii and L. macropodum are parasites of wild mammals while L. martiniquensis, L. orientalis and an unnamed Leishmania sp. from Ghana are infectious to humans. There is very little information on natural reservoir hosts and vectors for any Mundinia species.Experimental infections of guinea pigs with all five Mundinia species were performed. Animals were injected intradermally with 107 culture-derived promastigotes into both ear pinnae. The courses of infections were monitored weekly; xenodiagnoses were performed at weeks 4 and 8 post-infection using Lutzomyia migonei. The distribution of parasites in different tissues was determined post-mortem by conventional ... : داء الليشمانيات هو مرض بشري وحيواني تسببه طفيليات من جنس الليشمانيا، والتي تنقسم الآن إلى أربعة أجناس فرعية، الليشمانيا، فيانيا، سوروليشمانيا وموندينيا. الجنس الفرعي موندينيا، الذي تأسس في عام 2016، منتشر جغرافيًا على نطاق واسع، ويغطي توزيعه جميع القارات، باستثناء القارة القطبية الجنوبية. وهو يتألف من 5 أنواع ؛ L. enriettii و L. macropodum هي طفيليات من الثدييات البرية في حين أن L. martiniquensis و L. orientalis و leishmania sp. من غانا معدية للبشر. هناك القليل جدًا من المعلومات حول مضيفات ونواقل الخزانات الطبيعية لأي نوع من أنواع موندينيا. تم إجراء التهابات تجريبية لخنازير غينيا مع جميع أنواع موندينيا الخمسة. تم حقن الحيوانات داخل الجلد مع 107 برومستيغوت مشتقة من الثقافة في كل من صيوان الأذن. تمت مراقبة دورات العدوى أسبوعيًا ؛ تم إجراء التشخيصات الخارجية في الأسبوعين 4 و 8 بعد العدوى باستخدام Lutzomyia migonei. تم تحديد توزيع الطفيليات في الأنسجة المختلفة بعد الوفاة بواسطة تفاعل البوليميراز المتسلسل التقليدي. لم يلاحظ أي اختلافات كبيرة في الوزن بين الحيوانات المصابة ومجموعة التحكم. طورت الحيوانات المصابة بـ ...